PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP MINAT DAN HASIL BELAJAR SISWA KELAS V DI SDN 5 BARANDASI KECAMATAN LAU - Andi Paida; Darmawati; Jumriati; Mutmainnah; Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The use of digital media in social studies learning can increase elementary students' learning interest in learning. This study aims to find out about the role of using digital technology-based learning media in developing digital-based media for students, especially in the teaching and learning process of social studies material in elementary schools. The literature study approach is the method used in the research conducted. Where this research originates from several journals that are relevant to the topic of discussion within the scope of the Role of Technology-based Learning Media in Social Studies Learning in Elementary Schools and the application of digital media. The research results obtained are, the use of technology as a learning medium in the social studies learning process in elementary schools has an effect on social studies learning views that are able to increase motivation, learning outcomes of digital media in students.